2016
DOI: 10.1089/cbr.2016.2054
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of MUC5AC Expression Contributes to the Apoptosis and Cell Cycle Arrest of Colon Cancer Cells

Abstract: Deregulated expressions of mucins have been found in various malignancies and play a pivotal role in carcinogenesis. MUC5AC, as a secreted mucin, is reported to be aberrantly expressed during epithelial cancer progression, including colon cancer. However, the mechanisms of the oncoprotein MUC5AC in the initiation of colon cancer requires further investigation. Here, we collected colon cancer tissues (n = 20) and corresponding paracancerous tissues (n = 20) and found that the expression of MUC5AC was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Our results highlighted that MUC1 and MUC5AC mRNA and protein levels were notably up-regulated in tumor tissues when compared with the normal mucosa. A similar pattern was found in many other studies [2,10,15,23].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results highlighted that MUC1 and MUC5AC mRNA and protein levels were notably up-regulated in tumor tissues when compared with the normal mucosa. A similar pattern was found in many other studies [2,10,15,23].…”
Section: Discussionsupporting
confidence: 91%
“…In normal physiological conditions, secretory mucin MUC5AC is not expressed in the colonic mucosa, whereas its aberrant expression is observed during development of colon cancer [1,13,15,23,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic inhibition of MUC5AC in colon cancer cells impaired the colony-forming ability of these cells by reducing cell viability, increased apoptosis and G 1 cell cycle arrest. Interestingly, loss of MUC5AC dramatically repressed the cell migration and invasion of colon cancer cells (182).…”
Section: Functional and Mechanistic Implications Of Muc5ac In Cancermentioning
confidence: 98%
“…Unlike MUC2, the expression of MUC5AC can be found to different degrees during the development of CRC, specifically both in mucinous and nonmucinous adenocarcinomas. Using siRNA technology, Zhu et al knockdown the expression of MUC5AC in SW620 cells, a CRC cell line with high MUC5AC expression, and found that siMUC5AC significantly inhibited cell migration and invasion and induces cell apoptosis and G1-phase cell cycle arrest; these effects resulted in impaired colony formation (Zhu et al, 2016), suggesting that MUC5AC is a promising target for the treatment of colon cancer. Unsurprisingly, CRC patients with high MUC5 expression showed poor cell differentiation, a high lymph node metastasis rate and late stage CRC (Wang et al, 2017), which suggests that MUC5AC is a promoter of tumors.…”
Section: Muc5acmentioning
confidence: 99%